Boron-tethered oxidopyrylium-based [5 + 2] cycloadditions. (28th September 2022) - Corrie, Seth I.; Pearce, Aaron C.; Grabowski, Jacob P.; Randolph, Kee A.; Guo, Wentao; Tantillo, Dean J.; Andrew Mitchell, T.
Graphical abstract: Abstract: Oxidopyrylium-based [5 + 2] cycloadditions between diethanolamine appended silyloxypyrones and organoboronic acid derivatives were achieved. Evidence for the diethanolamine boronate (i.e. DABO) complex was observed by 1 H NMR at room temperature with boronic acids and [5 + 2] cycloaddition was achieved in a single reaction mixture in DCE. Pinacol boronates required elevated temperature (140 °C) in refluxing p-xylene but afforded access to products not readily available with boronic acids. Theoretical calculations provide evidence for an asynchronous concerted transition state. Good functional group tolerance was observed and products were isolated as the oxabicyclo[3.2.1]-octane DABO cycloadducts.